Narratives of Nationalism in Indonesia and Malaysia’s History Textbooks - Mulyana, Agus (History Department, Semarang State University and Historian Society of Indonesia, 2021)
History textbooks are historical writings that have a function in developing educational values, including nationalism. Indonesia has a historical background colonized by the West, so that history textbooks will create nationalism’s value. This study aims to see how nationalism is described in the history textbooks of the two countries through historical events. The method used in this research is content analysis, namely analyzing the textbook’s narrative based on the indicators of the theory of nationalism. The findings of this study are indicators of the idea of nationalism, which includes myths of past glory, ethnicity and diversity, and colonialism in the description of historical events. This study concludes that the indicators of nationalism in history textbooks in Indonesia and Malaysia narrate in an indoctrinating language by placing nationalism as an ideology.Buku teks sejarah adalah tulisan sejarah yang memiliki fungsi dalam mengembangkan nilai-nilai pendidikan, termasuk nasionalisme. Indonesia memiliki latar belakang sejarah yang dijajah oleh Barat, sehingga buku teks sejarah akan melahirkan nilai nasionalisme. Penelitian ini bertujuan untuk melihat bagaimana nasionalisme digambarkan dalam buku teks sejarah kedua negara melalui peristiwa sejarah. Metode yang digunakan dalam penelitian ini adalah analisis isi, yaitu menganalisis narasi buku teks berdasarkan indikator teori nasionalisme. Temuan penelitian ini adalah indikator gagasan nasionalisme, yang meliputi mitos kejayaan masa lalu, etnisitas dan keragaman, dan kolonialisme dalam deskripsi peristiwa sejarah. Penelitian ini menyimpulkan bahwa indikator nasionalisme dalam buku teks sejarah di Indonesia dan Malaysia dinarasikan dalam bahasa yang indoktrinasi dengan menempatkan nasionalisme sebagai ideologi.